Linguistic Relativity, Cultural Relativity, and Foreign Language Teaching - Ahmad Effendi Kadarisman (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: Every language is assumed to be unique, structurally and culturally. Taking this neo-Bloomfieldian assumption at the outset, this paper first points out the inadequacy of sentence grammars for foreign language teaching. Toward this end, the paper further argues for the necessity of understanding linguistic and cultural relativity. Linguistic relativity, or better known as the Sapir-Whorf hypothesis, suggests that the way we perceive and categorize reality is partly determined by the language we speak; and cultural relativity implies that verbalization of concepts in a particular language is often culturally conditioned. As related to the field of foreign language teaching, relativity across languages and cultures presupposes contrastive analysis in a very broad sense. Thus pointing out differences in language structures and cultural conventions should lead students to better acquisition of linguistic and cultural sensitivity.